2010
DOI: 10.1002/jemt.20940
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the growth, evolution, and self‐aggregation of β‐amyloid fibrils using tapping‐mode atomic force microscopy

Abstract: Amyloid peptide (Aβ) is the major protein component of plaques found in Alzheimer's disease, and the aggregation of Aβ into oligomeric and fibrillic assemblies has been shown to be an early event of the disease pathway. Visualization of the progressive evolution of nanoscale changes in the morphology of Aβ oligomeric assemblies and amyloid fibrils has been accomplished ex situ using atomic force microscopy (AFM) in ambient conditions. In this report, the size and the shape of amyloid β(1-40) fibrils, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
4
21
0
Order By: Relevance
“…This dimension is in very good agreement with that described by Serem et al for the small spherical oligomers which they can observe by AFM [45]. As described by the same authors, a fibrillar aggregation starts with the aging of the peptide solution to yield, after several weeks, a high peptide fibrillation.…”
Section: A 40supporting
confidence: 86%
“…This dimension is in very good agreement with that described by Serem et al for the small spherical oligomers which they can observe by AFM [45]. As described by the same authors, a fibrillar aggregation starts with the aging of the peptide solution to yield, after several weeks, a high peptide fibrillation.…”
Section: A 40supporting
confidence: 86%
“…The ability to circumvent the lag-phase of amyloid formation by adding preformed aggregates in a process called seeding (Jarrett and Lansbury, 1993; Lansbury, 1997; Paravastu et al, 2006; Nonaka et al, 2010; Jucker and Walker, 2011; Serem et al, 2011), demonstrating that such seeds can impose aberrant structure on other proteins. Such a phenomenon appears to play a role in the cell to cell translation of the disease state across specific regions of the brain (Vonsattel and DiFiglia, 1998; Braak et al, 2003; Ravits et al, 2007; Braak and Del Tredici, 2011), and this is reminiscent of the infectious nature of prions.…”
Section: The Interaction Of Prions With Surfaces and Parallels With Cmentioning
confidence: 99%
“…1113 It has been suggested in AFM studies that small Aβ oligomers act as seeds that induce oligomerization of adjacent monomers, similar to the mechanism of template-mediated prion conversion. 6,14,15 Studies using ion-mobility based mass spectrometry (IMS-MS) have attempted to address exactly which types of oligomers are formed and whether these oligomers act as seeds for fibril growth. 16,17 These studies revealed that even order oligomers were dominant, 2, 4, 6 and 12 with high populations of hexamers and dodecomers.…”
mentioning
confidence: 99%